Iron-based MOFs composite electrode and application thereof
By preparing iron-based MOFs composite electrodes, using Cu@Fe-ZIF mixed ligand to construct a graded porous electrocatalyst, the shuttle effect problem caused by changes in elemental sulfur volume of lithium sulfur batteries is solved, and higher capacity and more stable cycles are achieved performance.
Patent Information
- Application Number
- CN202411569719.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
During the lithiation process of lithium-sulfur batteries, polysulfide dissolves in the electrolyte due to the volume expansion and contraction of elemental sulfur, forming a "shuttle effect", reducing the efficiency of Coulomb, resulting in a far different actual capacity from the theoretical capacity.
Fe2O3@Cu@Fe-ZIF composite material was prepared by co-precipitation + hydrothermal method + multi-step ultrasonic + vacuum arc method, and Cu@Fe-ZIF mixed ligand was constructed to form a graded porous electrocatalyst and activity. Site, expose mass transfer capability, improve sulfur loading effect and battery performance.
It achieves a more stable electrode structure, higher capacity, better electrolyte contact and more stable long cycle performance, inhibiting the shuttle effect of lithium-sulfur batteries and improving cycle life and specific capacity.
Smart Images

Figure CN119447148A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and specifically relates to an iron-based MOFs composite electrode and applications thereof. Background Art
[0002] Lithium-sulfur batteries have the same high efficiency and extensive potential as lithium-ion batteries. Because lithium-sulfur batteries have high specific capacity of 1675mAh / g and high energy density of 2600Wh / kg, as well as low manufacturing cost and environmental friendliness, lithium-sulfur batteries have become one of the current research hotspots. However, the reaction of lithium-sulfur batteries is very complicated. The active substance elemental sulfur in the reaction process has volume expansion and contraction during the lithiation process. The polysulfide produced is very easy to dissolve in the electrolyte, forming a "shuttle effect", which reduces its coulomb efficiency, resulting in a large difference between the actual capacity of lithium-sulfur batteries and the theoretical capacity. Studies have found that elemental sulfur is not suitable for direct use as a positive electrode material because it is an insulator. It needs to be combined with a conductive material to improve the electrochemical performance and cycle life of lithium-sulfur batteries. Many researchers have proposed that sulfur be loaded on the surface of some matrix materials. These matrix materials can not only fix sulfur active materials, inhibit the dissolution and shuttling of polysulfides, but also improve the conductivity of sulfur. At present, the main types of matrix materials are carbon, inorganic metal compounds and conductive polymers. Inorganic metal compounds have a variety of chemical compositions, complex crystal structures and strong sulfur adsorption capacity. Among them, iron oxide (Fe2O3) is a common transition metal oxide because of its abundant reserves, safety, high power density and high theoretical capacity. 3+ It has a strong adsorption effect on sulfur and can increase the conductivity of the matrix. In the prior art, nano-iron oxide (Fe2O3) is synthesized by hydrothermal method, and it is prepared into electrode material after sulfur loading; the material has a large specific surface area and has a strong adsorption effect on sulfur, which can improve its electrochemical performance; after 200 cycles, the capacity retention rate can reach 77%. Furthermore, there is also a hydrothermal method to prepare Cu doped Fe2O3 (Cu@Fe2O3) with different mass ratios as sulfur-loaded matrix materials, and after sulfur loading, a Cu@Fe2O3 / S composite electrode material is obtained; under the condition of sulfur loading of 1:3, the first discharge specific capacity of this material at 0.2C can reach 887.91mAh·g-1, and the capacity retention rate can reach 45.7% after 200 cycles. Under the condition of sulfur loading of 1:4, the first discharge capacity at 0.2C can reach 808.96mAh·g-1, and the capacity retention rate after 200 cycles is as high as 63%; under the condition of sulfur loading of 1:5, the first discharge capacity at 0.2C can reach 970mAh·g-1, and the capacity retention rate after 200 cycles can reach 66.6%. However, Cu doping is formed by pyrolysis. Although it has small nanoparticles, the aggregation and accumulation of particles is uncontrollable, which leads to poor conductivity and degradation in high potential reactions under long-term charge and discharge, causing structural collapse, thereby affecting the cycle life. Summary of the invention
[0003] The purpose of the present invention is to provide an iron-based MOFs composite electrode and its application in view of the shortcomings in the current lithium-sulfur battery technology. The present invention can effectively alleviate the volume change of the material by introducing a strong and stable metal skeleton of ZIF, and realize appropriate size control. At the same time, the construction of Fe-ZIF mixed ligands is an effective means to improve the electrochemical stability of ZIF derivatives, which is conducive to the formation of hierarchical porous electrocatalysts and the exposure of active sites, thereby improving the mass transfer capacity. Compared with the existing material technology, it has a more stable electrode structure, higher capacity, better contact with the electrolyte and more stable long-cycle performance. Specifically, the iron-based MOFs composite electrode (Fe2O3@Cu@Fe-ZIF) is prepared by coprecipitation + hydrothermal method + multi-step ultrasound + vacuum arc method. The present invention selects Fe-ZIF material as a metal frame to be coated on the Cu surface, and synthesizes club-shaped nanosphere particles after mixing with Fe oxide, calcining, and DC vacuum arc method. Cu@Fe-ZIF can effectively increase the defect concentration in the Fe2O3 structure, provide more load space for subsequent components, such as sulfur, increase its load effect on sulfur, improve sulfur utilization, alleviate volume changes, and thus improve battery performance. If the Cu@Fe2O3 material is prepared by hydrothermal method, and the Cu@Fe2O3 sulfur-loaded matrix material is synthesized by DC vacuum arc method; transition metal (Cu) doping is formed by pyrolysis, although it has metal nanoparticles with smaller particles; the material after pyrolysis has high conductivity, but it is easy to aggregate metal particles, and the aggregation and oxidation of compound nanoparticles will lead to poor conductivity and degradation in high-potential reactions, and will also cause structural collapse under long-term charging and discharging, thereby affecting the cycle life.
[0004] The composite material of the present invention is first prepared by coprecipitation of Cu@Fe-ZIF powder, then prepared by hydrothermal reaction + step-by-step ultrasound + vacuum arc method Fe2O3@Cu@Fe-ZIF, and then fused with S at high temperature by hot melt method. Specifically, the purpose of the present invention is achieved by the following technical solutions:
[0005] <First aspect>
[0006] The present invention relates to an iron-based MOFs composite electrode material, which is prepared by a method comprising the following steps:
[0007] S1. Using copper salt, trivalent iron salt, dispersant and imidazole ligand as raw materials, Cu@Fe-ZIF powder was prepared by coprecipitation method;
[0008] S2, Fe(OH)3 colloid formed by hydrolysis of trivalent iron salt solution is mixed with the Cu@Fe-ZIF powder, and the sulfur-loaded matrix material Fe2O3@Cu@Fe-ZIF is prepared by hydrothermal reaction;
[0009] S3, using a graphite crucible as an anode and a tungsten rod as a cathode, placing the Fe2O3@Cu@Fe-ZIF material into the graphite crucible, and obtaining nano-Fe2O3@Cu@Fe-ZIF material at the cathode by a DC arc method;
[0010] S4. Using the nano-Fe2O3@Cu@Fe-ZIF material and sublimated sulfur as raw materials, the active material Fe2O3@Cu@Fe-ZIF@S for iron-based MOFs composite electrode is prepared by a hot melt method.
[0011] As an embodiment, in step S1, the copper salt is copper acetate, copper sulfate or copper nitrate.
[0012] As an embodiment, in step S1, the trivalent iron salt is ferric chloride hexahydrate.
[0013] As an embodiment, in step S1, the imidazole ligand is 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole or 2-phenylimidazole.
[0014] As an embodiment, in step S1, the dispersant is polyvinyl pyrrolidone.
[0015] As an embodiment, in step S1, the mass ratio of the copper salt, the trivalent iron salt, the dispersant and the imidazole ligand is 1:(1-4):(2-6):(1-3).
[0016] As an embodiment, in step S1, copper salt, trivalent iron salt, and dispersant are ultrasonically dispersed in a solvent to obtain a mixed solution A; imidazole ligand is dissolved in a solvent to obtain a mixed solution B; mixed solution A and mixed solution B are mixed, stirred, centrifuged, dried, and ground to obtain the Cu@Fe-ZIF powder. In some embodiments, solution B is pumped by a peristaltic pump (50-80 mL min -1 ) Slowly add drop by drop into solution A. After all the solution has been added, continue to stir for 30-60 minutes and then centrifuge.
[0017] As an embodiment, the rotation speed of the centrifugal treatment is 6000-8000 r·min -1 The drying time is 8-12 minutes and the number of times is 1-5 times. The drying temperature is 100-120°C and the time is 20-24 hours.
[0018] As an embodiment, in step S2, the molar ratio of the ferric salt to Cu@Fe-ZIF is 1:1 to 1:2.
[0019] As an embodiment, in step S2, the temperature of the hydrothermal reaction is 150-190°C, such as 150°C, 160°C, 170°C, 180°C, 190°C; and the time of the hydrothermal reaction is 2-3h.
[0020] As an embodiment, during the hydrothermal reaction, ultrasound is applied for 20-40 minutes every hour, with a power of 240-280 W and a frequency of 50-70 Hz.
[0021] As an embodiment, in step S2, after the hydrothermal reaction is completed, the material is dried at 100-120°C for 20-24 hours and then ground to obtain the sulfur-loaded matrix material Fe2O3@Cu@Fe-ZIF.
[0022] In the process of preparing the Fe2O3@Cu-Fe-ZIF composite material, the present invention first prepares Fe(OH)3 colloid, then dopes Cu-Fe-ZIF, and finally prepares the nano-level composite material by vacuum arc method.
[0023] As an embodiment, in step S2, the ferric iron salt is ultrasonically dissolved to form a ferric iron salt aqueous solution, which is then added dropwise into boiling water. 3+ Gradually hydrolyze to form Fe(OH)3 colloid.
[0024] As an implementation scheme, in step S3, the reaction process of the DC arc method is: evacuate the reaction chamber to 1-5 Pa, and then introduce dry air into the reaction chamber until the internal pressure reaches 10-12 kPa; turn on the cooling device, start the arc control power supply, and make the material react rapidly; at this time, the input current is 100-110A, the arc voltage is 20-22V, and as the arc time increases, the gas pressure and arc voltage gradually increase; when the arc voltage reaches 22-24V and the gas pressure rises to 12-14 kPa, continue to discharge for 5-7 minutes and then turn off the power; then continue to keep the sample in the reaction chamber for 6-10 hours.
[0025] As an embodiment, in step S4, the mass ratio of the nano-Fe2O3@Cu@Fe-ZIF material to the sublimated sulfur is 1:(0.5-3).
[0026] As an embodiment, in step S4, the hot melt method is to carry out a constant temperature reaction at 155-175° C. for 17-20 hours under vacuum conditions.
[0027] <Second Aspect>
[0028] The present invention also relates to an iron-based MOFs composite electrode, wherein the composite electrode uses the above-mentioned material Fe2O3@Cu@Fe-ZIF@S as an active material.
[0029] As an embodiment, the composite electrode further contains a conductive carbon material and a binder.
[0030] As an embodiment, in the composite electrode, the mass ratio of the materials Fe2O3@Cu@Fe-ZIF@S, the conductive carbon material and the binder is (7-8):(1-3):(1-3).
[0031] As an embodiment, the conductive carbon material is Super-P conductive carbon black.
[0032] As an embodiment, the binder is PVDF.
[0033] The raw materials involved in the preparation method of the above-mentioned lithium-sulfur battery positive electrode material are all obtained through commercial purchase.
[0034] <Third Aspect>
[0035] The present invention also relates to the use of the aforementioned iron-based MOFs composite electrode, or the aforementioned material for the iron-based MOFs composite electrode in the preparation of a lithium-sulfur battery.
[0036] The present invention proposes a method for preparing an iron-based MOFs composite electrode, and applies it to lithium-sulfur batteries, which can play a good role in suppressing the shuttling effect of polysulfide discharge products, thereby improving the cycle life and specific capacity of lithium-sulfur batteries. Specifically, zeolite imidazolate framework material derivatives (ZIFs) and their derivatives have the characteristics of structural designability and controllable chemical composition. The present invention introduces a strong and stable metal skeleton of ZIF through nanostructure engineering to effectively alleviate the volume change of alloy-type materials and achieve appropriate size control. Compared with the original alloy-type material, the ZIF-derived alloy-type material has a more stable electrode structure, higher capacity, better contact with the electrolyte, and more stable long-cycle performance. At the same time, the construction of mixed ligands is an effective means to improve the electrochemical stability of ZIF derivatives, which is conducive to the formation of hierarchical porous electrocatalysts and the exposure of active sites, thereby improving the mass transfer capacity.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The present invention prepares iron oxide (Fe2O3) and metal oxide Fe2O3@Cu@Fe-ZIF by hydrothermal method + multi-step ultrasound + vacuum arc ignition. Multi-step ultrasound has the advantages of fast reaction time, uniform heating, morphology control, small particles, etc., and can effectively control the size and uniformity of the particles.
[0039] (2) The Cu@Fe-ZIF mixed ligand has the characteristics of large specific surface area and large porosity. The construction of this ligand is conducive to the formation of hierarchical porous electrocatalysts and exposure of active sites, reducing the aggregation of metal particles to adapt to the volume changes caused by the charge and discharge process. At the same time, more surface active sites are introduced by heteroatom (Cu) doping to expand the interlayer spacing to accelerate the transmission of Li+, thereby inhibiting the shuttle effect of lithium-sulfur batteries, improving the stability of the structure, and thus improving the cycle performance of the battery; in addition, Cu@Fe-ZIF can effectively increase the defect concentration in the Fe2O3 structure, providing more loading space for subsequent components such as sulfur, increasing its loading effect on sulfur, improving the utilization rate of sulfur, alleviating volume changes, and thus improving battery performance;
[0040] (3) The nanoscale Fe2O3@Cu@Fe-ZIF prepared by the DC vacuum arc method has better surface properties (hammer-shaped nanoparticles, uniform particles, and large specific surface area), providing better conditions for sulfur loading. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0042] Figure 1 Comparative SEM images of Fe2O3@Cu vacuum arc method and Fe2O3@Cu-@Fe-ZIF sulfur-supported matrix material before and after vacuum arc method; a is Fe2O3@Cu without vacuum arc method; b is Fe2O3@Cu after vacuum arc method; c is nanocomposite Fe2O3@Cu-@Fe-ZIF material prepared by vacuum arc method;
[0043] Figure 2 A comparison chart of the cycle life of the Fe2O3@Cu@Fe-ZIF vacuum arc method and the Fe2O3@Cu composite electrode material prepared in Example 2 at room temperature;
[0044] Figure 3 This is a comparison diagram of the electrochemical impedance of the Fe2O3@Cu@Fe-ZIF and Fe2O3@Cu composite electrode materials prepared in Example 3. DETAILED DESCRIPTION
[0045] The present invention is further illustrated by the following examples, but any example or combination thereof should not be construed as limiting the scope or implementation of the present invention. Without departing from the spirit and scope of the present invention, those skilled in the art may make any modifications or changes to the technical solution of the present invention, and such modifications and changes are also included in the scope of the present invention.
[0046] In the examples, if the specific conditions are not specified, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for all reagents or instruments, they are all conventional products that can be purchased commercially. In order to better illustrate the present invention, numerous specific details are provided in the specific embodiments below. It should be understood by those skilled in the art that the present invention can be implemented equally without certain specific details. In other embodiments, methods, means, equipment and steps well known to those skilled in the art are not described in detail to highlight the gist of the present invention.
[0047] Example 1
[0048] 1. Preparation of Fe2O3@Cu@Fe-ZIF:
[0049] 1.2 g of copper acetate, 3.6 g of ferric chloride hexahydrate and 4.8 g of polyvinyl pyrrolidone were ultrasonically dispersed in 80 mL of methanol, and the mixed solution was marked as solution A. 2.4 g of 2-methylimidazole was fully dissolved in 80 mL of methanol, and the mixed solution was marked as mixed solution B. Solution B was pumped by a peristaltic pump (60 mL min) through coprecipitation. -1 ) was slowly added drop by drop into solution A, and stirring was continued for 50 min after all the addition was completed. Finally, centrifugation was performed at a speed of 7000 r / min -1 , time is 10min, number of times is 3 times, drying is carried out at 110℃ for 20h, and grinding is carried out to obtain Cu@Fe-ZIF powder.
[0050] Then, 2.7 g of ferric chloride hexahydrate was weighed into 50 mL of deionized water using an electronic balance and placed in an ultrasonic cleaner to fully dissolve it with the help of ultrasound. Then, 10 mL of FeCl3 solution was added dropwise into 100 mL of boiling water. 3+ It will be gradually hydrolyzed, and then fully mixed with Cu@Fe-ZIF powder (ferric chloride hexahydrate and Cu@Fe-ZIF powder in a molar ratio of 1:1), and transferred to a hydrothermal reactor. At a hydrothermal temperature of 150°C and a time of 3 hours, ultrasonic waves are applied every 1 hour for 30 minutes, with a power of 260W and a frequency of 50HZ. After drying at 100°C for 24 hours, the Cu@Fe-ZIF doped Fe2O3 sulfur-loaded matrix material Fe2O3@Cu@Fe-ZIF is obtained by grinding.
[0051] Second, preparation of Fe2O3@Cu material:
[0052] First, 4.10 g of ferric chloride hexahydrate (FeCl3·6H2O) was weighed into 75 mL of deionized water using an electronic balance, and then placed in an ultrasonic cleaner to fully dissolve it with the help of ultrasound to obtain a 0.2 mol / L ferric chloride (FeCl3) solution. Then, 10 mL of the FeCl3 solution was added dropwise into 100 mL of boiling water. 3+ It will be gradually hydrolyzed, and then fully mixed with copper acetate at a mass ratio of 1:1.5 (ferric chloride hexahydrate and copper acetate), and transferred to a hydrothermal kettle. At a hydrothermal temperature of 150°C and a time of 3 hours, ultrasonic waves are applied every 1 hour for 30 minutes, with a power of 260W and a frequency of 50HZ. After drying at 100°C for 24 hours, the material Fe2O3@Cu is obtained by grinding.
[0053] 3. Preparation of nanocomposite Fe2O3@Cu@Fe-ZIF materials:
[0054] The DC arc method uses a fully cooled graphite crucible as the anode and a tungsten rod with a purity greater than 99.99%, a diameter of 8 mm and a length of 30 cm as the cathode.
[0055] The Fe2O3@Cu@Fe-ZIF and Fe2O3@Cu were subjected to the following steps respectively:
[0056] Put it into a graphite crucible; the graphite crucible has good stability and high conductivity to promote the rapid start of the DC arc; evacuate the reaction chamber to 4pa, and then pass dry air into the reaction chamber until the internal pressure reaches 10kpa; turn on the cooling device, start the arc control power supply, and make the material react quickly; at this time, the input current is 100A, the arc voltage is 20V, and as the arc time increases, the gas pressure and arc voltage gradually increase; when the arc voltage reaches 22V and the gas pressure rises to 12kpa, continue to discharge for 5min and then turn off the power. Then, continue to keep the sample in the reaction chamber for 7h to allow Fe, O and Cu to fully contact. Finally, near the tip of the cathode tungsten rod, the desired nanocomposite powder can be obtained (Fe2O3@Cu@Fe-ZIF corresponds to the nanocomposite Fe2O3@Cu@Fe-ZIF material; Fe2O3@Cu corresponds to the nanocomposite Fe2O3@Cu material).
[0057] Figure 1The SEM images of Fe2O3@Cu and Fe2O3@Cu@Fe-ZIF sulfur-bearing matrix materials before and after vacuum arc treatment are compared. (b) is the material Fe2O3@Cu obtained by vacuum arc treatment, which has a smooth surface, close arrangement, large pores, slight agglomeration, and a particle size significantly smaller than that of the material (a) not subjected to vacuum arc treatment. (c) is the material Fe2O3@Cu@Fe-ZIF obtained by vacuum arc treatment. The magnified SEM photo shows that the surface of the material is a nano baseball-like morphology, the particle size is significantly smaller than that of Fe2O3@Cu, and the specific surface area is significantly larger than that of Fe2O3@Cu. It can also be seen from the SEM comparison that after the introduction of ZIF, the morphology of the material changes, the particle size is uniform, the distribution is dense and not stacked, and the pore structure is effectively regulated, which can alleviate the volume expansion caused by charging and discharging. Through research, it can be seen that this coral cluster-like matrix material can increase the adsorption strength of sulfur, while inhibiting the shuttle effect and improving conductivity. As a sulfur composite electrode material, it can effectively improve the utilization rate of sulfur and reduce problems such as sulfur volume expansion during charging and discharging.
[0058] Example 2
[0059] 1. Preparation of Fe2O3@Cu@Fe-ZIF:
[0060] 1.2 g of copper acetate, 3.6 g of ferric chloride hexahydrate and 4.8 g of polyvinyl pyrrolidone were ultrasonically dispersed in 80 mL of methanol, and the mixed solution was marked as solution A. 2.4 g of 2-methylimidazole was fully dissolved in 80 mL of methanol, and the mixed solution was marked as mixed solution B. Solution B was pumped by a peristaltic pump (60 mL min) through coprecipitation. -1 ) was slowly added drop by drop into solution A, and stirring was continued for 50 min after all the addition was completed. Finally, centrifugation was performed at a speed of 8000 r / min -1 , time is 10min, number of times is 3 times, drying is carried out at 120℃ for 20h, and grinding is carried out to obtain Cu@Fe-ZIF powder.
[0061] Then, 2.7 g of ferric chloride hexahydrate was weighed into 50 mL of deionized water using an electronic balance and placed in an ultrasonic cleaner to fully dissolve it with the help of ultrasound. Then, 10 mL of FeCl3 solution was added dropwise into 100 mL of boiling water. 3+It will be gradually hydrolyzed, and then fully mixed with Cu@Fe-ZIF powder (ferric chloride hexahydrate and Cu@Fe-ZIF powder in a molar ratio of 1:1, 1:1.5, and 1:2, respectively), and transferred to a hydrothermal kettle. At a hydrothermal temperature of 170°C and a time of 2h, ultrasonic waves are applied every 1 hour for 30min, with a power of 280W and a frequency of 50HZ. After drying at 120°C for 20h, the Cu@Fe-ZIF doped Fe2O3 sulfur-loaded matrix material Fe2O3@Cu@Fe-ZIF is obtained by grinding.
[0062] 2. Preparation of nanocomposite Fe2O3@Cu@Fe-ZIF materials:
[0063] The DC arc method uses a fully cooled graphite crucible as the anode and a tungsten rod with a purity greater than 99.99%, a diameter of 8 mm and a length of 30 cm as the cathode.
[0064] The three Fe2O3@Cu@Fe-ZIF prepared in three different ratios (molar ratio of ferric chloride hexahydrate to Cu@Fe-ZIF) prepared in step 1 were subjected to the following steps:
[0065] Put it into a graphite crucible; the graphite crucible has good stability and high conductivity to promote the rapid start of the DC arc. Evacuate the reaction chamber to below 4Pa, and then pass dry air into the reaction chamber until the internal pressure reaches 10kPa. Turn on the cooling device and start the arc control power supply to make the material react quickly. At this time, the input current is 100A, the arc voltage is 20V, and as the arc time increases, the gas pressure and arc voltage gradually increase. When the arc voltage reaches 22V and the gas pressure rises to 12kPa, continue to discharge for 5min and then turn off the power. Then, continue to keep the sample in the reaction chamber for 7h to allow Fe, O and Cu to fully contact. Finally, the desired nano-composite powder can be obtained near the tip of the cathode tungsten rod.
[0066] 3. Preparation of nanocomposite Fe2O3@Cu materials:
[0067] First, use an electronic balance to weigh 2.70g of ferric chloride hexahydrate (FeCl3·6H2O) in 50mL of deionized water, and put it into an ultrasonic cleaner to fully dissolve it with the help of ultrasound. Then, add 10mL of FeCl3 solution dropwise into 100mL of boiling water. 3+ It will be gradually hydrolyzed, and then mixed with copper acetate in a mass ratio of 1:1.5 (ferric chloride hexahydrate and copper acetate), and transferred to a hydrothermal kettle. At a hydrothermal temperature of 150°C and a time of 3 hours, ultrasonic waves are applied every 1 hour for 30 minutes, with a power of 260W and a frequency of 50HZ. After drying at 100°C for 24 hours, Fe2O3@Cu is obtained by grinding.
[0068] Put Fe2O3@Cu into a graphite crucible. Graphite crucible has good stability and high conductivity to promote the rapid start of DC arc. Evacuate the reaction chamber to 4Pa, and then pass dry air into the reaction chamber until the internal pressure reaches 10kPa. Turn on the cooling device and start the arc control power supply to make the material react quickly. At this time, the input current is 100A, the arc voltage is 20V, and as the arc time increases, the gas pressure and arc voltage gradually increase. When the arc voltage reaches 22V and the gas pressure rises to 12kPa, the power supply is turned off after continuous discharge for 5min. Then, continue to keep the sample in the reaction chamber for 7h to allow Fe, O and Cu to fully contact. Finally, the desired nanocomposite powder can be obtained near the tip of the cathode tungsten rod.
[0069] 4. Preparation of nanocomposite Fe2O3@Cu@Fe-ZIF@S materials:
[0070] Using the hot melt method, the three different ratios (three molar ratios of hexahydrate ferric chloride to Cu@Fe-ZIF) of nanocomposite Fe2O3@Cu@Fe-ZIF materials and nanocomposite Fe2O3@Cu materials obtained in the above steps were respectively ground with sublimed sulfur at a mass ratio of 1:2, and then kept at a constant temperature of 175°C in a vacuum drying oven for 17 hours. After the heating was completed, it was cooled to room temperature, fully ground and sieved, and finally the desired iron-based MOFs composite electrode Fe2O3@Cu@Fe-ZIF@S and nanocomposite Fe2O3@Cu@S were obtained.
[0071] 5. The three different proportions of Fe2O3@Cu@Fe-ZIF@S and nanocomposite Fe2O3@Cu@S were mixed with Super-P conductive carbon black and PVDF binder at a mass ratio of 7:2:1, dispersed in NMP after mixing, placed on a magnetic stirrer, and stirred for 24 hours to obtain the active material slurry. The stirred slurry was coated on the surface of 15μm thick aluminum foil (double-sided coating, the thickness of the single-sided coating was 1mm), and vacuum dried at 50℃ for 24 hours. Finally, the electrode was cut into circular electrode sheets with a diameter of 10mm using a slicer and assembled into a battery, in which the negative electrode was a lithium sheet, the electrolyte was: EC, DMC and FEC mass ratio was 5:4:1, and LiPF6, the content of LiPF6 in the electrolyte was 1M.
[0072] Figure 2 The charge-discharge cycle performance of the battery assembled from the three Fe2O3@Cu@Fe-ZIF@S composite electrode materials and the nanocomposite Fe2O3@Cu@S material prepared in this embodiment is compared, wherein the charge-discharge cycle test method is: 0.2C constant current constant voltage charging to 3.65V, the cut-off current is 0.05C; 0.2C discharge to 2.5V; Figure 2 It can be seen that with the increase of Fe-ZIF content, the cycle performance of the battery has declined. When Fe2O3:Cu@Fe-ZIF=1:1.5, the composite electrode material has the highest discharge capacity. After 400 charge and discharge cycles, the discharge capacity can still reach more than 400mAh / g, which is much higher than other groups. This shows that under this condition, the Fe-ZIF ligand strengthens the fit between sulfur and Fe2O3@Cu matrix material, making the structure between them more stable, and has a very strong adsorption capacity with sulfur. Therefore, while having a high discharge capacity, it can also maintain very good cycle stability.
[0073] Example 3
[0074] 1. Preparation of Fe2O3@Cu@Fe-ZIF:
[0075] 1.2 g of copper acetate, 3.6 g of ferric chloride hexahydrate and 4.8 g of polyvinyl pyrrolidone were ultrasonically dispersed in 80 mL of methanol, and the mixed solution was marked as solution A. 2.4 g of 2-methylimidazole was fully dissolved in 80 mL of methanol, and the mixed solution was marked as mixed solution B. Solution B was pumped by a peristaltic pump (80 mL min) through coprecipitation. -1 ) was slowly added drop by drop into solution A, and stirring was continued for 60 min after all the addition was completed. Finally, centrifugation was performed at a speed of 7000 r / min -1 , time is 10min, number of times is 3 times, drying is carried out at 100℃ for 24h, and grinding is carried out to obtain Cu@Fe-ZIF powder.
[0076] Then, 2.7 g of ferric chloride hexahydrate was weighed into 50 mL of deionized water using an electronic balance and placed in an ultrasonic cleaner to fully dissolve it with the help of ultrasound. Then, 10 mL of FeCl3 solution was added dropwise into 100 mL of boiling water. 3+ It will be gradually hydrolyzed, and then fully mixed with Cu@Fe-ZIF powder (ferric chloride hexahydrate and Cu@Fe-ZIF powder in molar ratios of 1:1, 1:1.5, and 1:2, respectively), and transferred to a hydrothermal reactor. At a hydrothermal temperature of 150°C and a time of 3 hours, ultrasonic waves are applied every hour for 30 minutes at a power of 240W and a frequency of 50HZ. After drying at 100°C for 24 hours, the Cu@Fe-ZIF doped Fe2O3 sulfur-loaded matrix material Fe2O3@Cu@Fe-ZIF is obtained by grinding.
[0077] 2. Preparation of nanocomposite Fe2O3@Cu@Fe-ZIF materials:
[0078] The DC arc method uses a fully cooled graphite crucible as the anode and a tungsten rod with a purity greater than 99.99%, a diameter of 8 mm and a length of 30 cm as the cathode.
[0079] The three Fe2O3@Cu@Fe-ZIF prepared in three different ratios (molar ratio of ferric chloride hexahydrate to Cu@Fe-ZIF) prepared in step 1 were subjected to the following steps:
[0080] Put it into a graphite crucible. The graphite crucible has good stability and high conductivity to promote the rapid start of the DC arc. Evacuate the reaction chamber to 4Pa, and then pass dry air into the reaction chamber until the internal pressure reaches 10kPa. Turn on the cooling device and start the arc control power supply to make the material react quickly. At this time, the input current is 100A, the arc voltage is 20V, and as the arc time increases, the gas pressure and arc voltage gradually increase. When the arc voltage reaches 22V and the gas pressure rises to 12kPa, continue to discharge for 5min and then turn off the power. Then, continue to keep the sample in the reaction chamber for 7h to allow Fe, O and Cu to fully contact. Finally, the desired nano-composite powder can be obtained near the tip of the cathode tungsten rod.
[0081] 3. Preparation of nanocomposite Fe2O3@Cu materials:
[0082] First, use an electronic balance to weigh 2.70g of ferric chloride hexahydrate (FeCl3·6H2O) in 50mL of deionized water, and put it into an ultrasonic cleaner to fully dissolve it with the help of ultrasound. Then, add 10mL of FeCl3 solution dropwise into 100mL of boiling water. 3+ It will be gradually hydrolyzed, and then fully mixed with copper acetate at a mass ratio of 1:1.5 (ferric chloride hexahydrate and copper acetate), and transferred to a hydrothermal kettle. At a hydrothermal temperature of 150°C and a time of 3 hours, ultrasonic waves are applied every 1 hour for 30 minutes, with a power of 260W and a frequency of 50HZ. After drying at 100°C for 24 hours, Fe2O3@Cu is obtained by grinding.
[0083] Put Fe2O3@Cu into a graphite crucible. Graphite crucible has good stability and high conductivity to promote the rapid start of DC arc. Evacuate the reaction chamber to 4Pa, and then pass dry air into the reaction chamber until the internal pressure reaches 10kPa. Turn on the cooling device and start the arc control power supply to make the material react quickly. At this time, the input current is 100A, the arc voltage is 20V, and as the arc time increases, the gas pressure and arc voltage gradually increase. When the arc voltage reaches 22V and the gas pressure rises to 12kPa, the power supply is turned off after continuous discharge for 5min. Then, continue to keep the sample in the reaction chamber for 7h to allow Fe, O and Cu to fully contact. Finally, the desired nanocomposite powder can be obtained near the tip of the cathode tungsten rod.
[0084] 4. Preparation of nanocomposite Fe2O3@Cu@Fe-ZIF@S materials:
[0085] Using the hot melt method, the three different ratios of nanocomposite Fe2O3@Cu@Fe-ZIF materials and nanocomposite Fe2O3@Cu materials obtained in the above steps (three molar ratios of ferric chloride hexahydrate to Cu@Fe-ZIF) were respectively ground with sublimed sulfur according to a mass ratio of 1:2, and then kept at a constant temperature of 155°C in a vacuum drying oven for 20 hours. After the heating was completed, it was cooled to room temperature, fully ground and sieved, and finally the desired iron-based MOFs composite electrodes Fe2O3@Cu@Fe-ZIF@S and Fe2O3@Cu@S were obtained.
[0086] 5. The three different proportions of Fe2O3@Cu@Fe-ZIF@S and nanocomposite Fe2O3@Cu@S were mixed with Super-P conductive carbon black and PVDF binder at a mass ratio of 7:2:1, dispersed in NMP after mixing, placed on a magnetic stirrer, and stirred for 24 hours to obtain the active material slurry. The stirred slurry was coated on the surface of 15μm thick aluminum foil (double-sided coating, single-sided coating thickness is 1mm), and vacuum dried at 50℃ for 24 hours. Finally, the electrode sheet was cut into a circular electrode sheet with a diameter of 10mm using a slicer and assembled into a battery, in which the negative electrode sheet was a lithium sheet, the electrolyte was: EC, DMC and FEC mass ratio was 5:4:1, and LiPF6, the content of LiPF6 in the electrolyte was 1M.
[0087] Figure 3 This is the EIS spectrum at 100% SOC, with a measurement frequency range of 10 6 ~10 -3 Hz. The EIS spectrum test method is: when applying the polarization signal, the amplitude of the sine wave potential is limited to 5mV, and the measurement frequency range is 10 6 ~10 -3Hz. The state of charge of the battery cell is 100% SOC.
[0088] By comparison, it can be seen that with the increase of Fe-ZIF content, the charge impedance of the battery increases. When Fe2O3:Cu@Fe-ZIF=1:1.5, the composite electrode material has the smallest electrochemical impedance arc radius, and in the low-frequency region, it has the largest linear slope. This shows that the Cu@Fe-ZIF mixed ligand can effectively reduce the charge impedance of the battery, and this conclusion is consistent with the cycle performance.
[0089] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. An iron-based MOFs composite electrode material, characterized in that: The material is prepared by a method comprising the following steps: S1. Using copper salt, trivalent iron salt, dispersant and imidazole ligand as raw materials, Cu@Fe-ZIF powder was prepared by coprecipitation method; S2, Fe(OH)3 colloid formed by hydrolysis of trivalent iron salt solution is mixed with the Cu@Fe-ZIF powder, and the sulfur-loaded matrix material Fe2O3@Cu@Fe-ZIF is prepared by hydrothermal reaction; S3, using a graphite crucible as an anode and a tungsten rod as a cathode, placing the Fe2O3@Cu@Fe-ZIF material into the graphite crucible, and obtaining nano-Fe2O3@Cu@Fe-ZIF material at the cathode by a DC arc method; S4. Using the nano-Fe2O3@Cu@Fe-ZIF material and sublimated sulfur as raw materials, the active material Fe2O3@Cu@Fe-ZIF@S for iron-based MOFs composite electrode is prepared by a hot melt method.
2. The iron-based MOFs composite electrode material according to claim 1, characterized in that: Step S1, the copper salt is copper acetate, copper sulfate or copper nitrate; the trivalent iron salt is ferric chloride hexahydrate; the imidazole ligand is 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole or 2-phenylimidazole; the dispersant is polyvinyl pyrrolidone; And / or, the mass ratio of the copper salt, the trivalent iron salt, the dispersant and the imidazole ligand is 1:(1-4):(2-6):(1-3).
3. The iron-based MOFs composite electrode material according to claim 1, characterized in that: In step S1, copper salt, trivalent iron salt and dispersant are ultrasonically dispersed in a solvent to obtain a mixed solution A; imidazole ligand is dissolved in a solvent to obtain a mixed solution B; mixed solution A and mixed solution B are mixed, stirred, centrifuged, dried and ground to obtain the Cu@Fe-ZIF powder.
4. The iron-based MOFs composite electrode material according to claim 3, characterized in that: The rotation speed of the centrifugal treatment is 6000-8000 r·min -1 , time is 8-12min, number of times is 1-5 times; And / or, the drying temperature is 100-120° C. and the drying time is 20-24 hours.
5. The iron-based MOFs composite electrode material according to claim 1, characterized in that: In step S2, the molar ratio of the ferric salt to the Cu@Fe-ZIF is 1:1 to 1:
2. And / or, the temperature of the hydrothermal reaction is 150-190° C. and the time is 2-3 h; and / or, during the hydrothermal reaction, ultrasound is applied for 20-40 minutes every hour at a power of 240-280 W and a frequency of 50-70 Hz; And / or, after the hydrothermal reaction is completed, the material is dried at 100-120° C. for 20-24 hours and then ground to obtain the sulfur-loaded matrix material Fe2O3@Cu@Fe-ZIF.
6. The iron-based MOFs composite electrode material according to claim 1, characterized in that: In step S2, the ferric iron salt is ultrasonically dissolved to form a ferric iron salt aqueous solution, which is then added dropwise into boiling water. 3+ Gradually hydrolyze to form Fe(OH)3 colloid.
7. The iron-based MOFs composite electrode material according to claim 1, characterized in that: In step S3, the reaction process of the DC arc method is: evacuate the reaction chamber to 1-5pa, and then introduce dry air into the reaction chamber until the internal pressure reaches 10-12kpa; turn on the cooling device, start the arc control power supply, and make the material react rapidly; at this time, the input current is 100-110A, the arc voltage is 20-22V, and as the arc time increases, the gas pressure and arc voltage gradually increase; when the arc voltage reaches 22-24V and the gas pressure rises to 12-14kpa, continue to discharge for 5-7min and then turn off the power; then continue to keep the sample in the reaction chamber for 6-10h.
8. The iron-based MOFs composite electrode material according to claim 1, characterized in that: In step S4, the mass ratio of the nano-Fe2O3@Cu@Fe-ZIF material to the sublimated sulfur is 1:(0.5-3); And / or, the hot melt method is a constant temperature reaction at 155-175° C. for 17-20 hours under vacuum conditions.
9. An iron-based MOFs composite electrode, characterized in that: The composite electrode uses the material Fe2O3@Cu@Fe-ZIF@S as described in any one of claims 1 to 8 as an active material.
10. Use of the iron-based MOFs composite electrode as claimed in claim 9, or the material as claimed in any one of claims 1 to 8 in the preparation of a lithium-sulfur battery.
Citation Information
Cited By
Preparation method of negative plate, negative plate and lithium ion battery
CN121601594A